Healthy Food Awareness Movement: Educating and Supporting Consumers in Choosing KERUPUK LAPIS - Novriyanti Lubis; lindayani lindayani; Asmufadiya Asmufadiya; Ihsan Saputra (Fakultas Kewirausahaan Universitas Garut, 2026)
Kerupuk are dry food snacks made from flour or rice with fish meat and other ingredients. Kerupuk Lapis are a variant that is quite widely consumed by consumers, having a colorful characteristic that in the manufacturing process uses dyes, such as those produced by factory X in Sukawening District. The purpose of this PKM is to provide counseling to consumers on how to choose safe Kerupuk Lapis carried out by a community service team from the Pharmacy Department of Garut University and to determine the quality of Kerupuk products based on organoleptic. The methods used were industrial visits, interviews, education and questionnaires. The results showed that 53% of respondents consumed kerupuk twice a week, 63.7% kerupuk as a meal complement. Meanwhile, regarding product quality, 90% thought kerupuk had a crunchy texture, and 50% thought they tasted good and were affordable, and the color of the kerupuk uses 16.7% synthetic dyeI. In the future, it is hoped that consumers will be wiser in choosing and consuming Kerupuk.